WEB-ORIENTED INFORMATION-EDUCATION ENVIRONMENT OF THE INSTITUTION OF GENERAL SECONDARY EDUCATION - Vorozhbyt A. (Kherson State University, 2018)
The article presents the model of the informational and educational environment of the institution of general secondary education - a system consisting of a set of subsystems (educational resources) that are in the conditions of information exchange between the participants of the educational process on the basis of modern web-oriented technologies. The main place in the model is LCMS MOODLE as a "point of access" to the knowledge of education. According to the analysis of educational management systems in scientific sources, it can be noted that in all the systems under consideration, access to educational materials is organized, interaction between teacher and pupil is provided, testing and reporting. Free use, the ability to add new functionality, points to the promising use of LCMS MOODLE in general secondary education. Other components of the system are considered: electronic portfolio system, social networking pages, communication tools (messengers), sites of educational institution, district administration of education, Ministry of Education and Science of Ukraine, Small academy of sciences, student subject competitions, competitions, etc. The model of the informational and educational environment of the institution of general secondary education can be modified, which is caused by constant changes in the information society and trends of use of ICT.